Evaluation of Hematological Parameters of Thyroid Disorders in Patients with Rheumatoid Arthritis in Wasit Governorate - Rahemmah, Ahmed Ismaeel; Al-Moussawi, Nisreen Habib (American Journal of Biology and Natural Sciences, 2025)
The study aims to find out the relationship between hypothyroidism, hyperthyroidism and rheumatoid disease in general in the individuals of the study sample, as well as to predict cases of hyperthyroidism and hypothyroidism in rheumatoid arthritis patients, predict the diseases that may result from this and find solutions to reduce them, as well as to study some hematological indicators that give a clear indication of hypothyroidism or hyperthyroidism in rheumatoid patients, and the influence of factors: smoking, genetic history of the disease, body mass index, age and gender of the patient on the levels of hematological indicators. This study was conducted in Wasit governorate at Al-Karama educational hospital and in coordination with the Endocrinology Center at Al-Zahra educational hospital located in Kut city and in coordination with the medical rehabilitation, physiotherapy and arthroplasty Center in Kut, for the period from October 1-2023 to April 21-2024, the study included (94) samples as a total group and included (61) female and (33) male, and included: (50) individuals as a control group and (44) individuals as a patient group, and included three age groups(21 - 29), (30 - 49) and (50-76) where they were divided into three groups as follows: 1-the first group: 37 patients: (25) female and (12) male with hypothyroidism aged (22-65) years. 2-the second Group: 7 patients: (4) females and (3) males with hyperthyroidism, aged (30-76) years. 3-the third group: 50 healthy individuals: (32) female and (18) male representing the control group, aged (21-75) years. The results of the study showed, in general, when comparing the patient group with the control group, a significant increase in Esr and a significant decrease in Pcv, Hb, Wbc, Hct, where the p-value was less than or equal to (0.05), as for the effect of the smoking factor on Esr, where there was a significant increase and the p-value was less than (0.05), as for the effect of the smoking factor on the parameters: Pcv, Hb, Wbc, Hct the presence of a significant decrease and the p-value is less than (0.05). With regard to the influence of the genetic history factor of the disease on the mentioned blood parameters, it turns out that there is no significant effect on those parameters and the p-value is greater than (0.05). As for the Bmi effect on Esr, we find that there is a significant increase and the p-value is less (0.05), while we find from the Bmi effect on the blood parameters: Pcv, Hb, Wbc, Hct that there is a significant decrease and the p-value is less than (0.05). As for the effect of the age factor on the ESR parameter, we find that there is a significant increase and the p-value is less than or equal to (0.05), and from knowing the effect of age on the blood parameters: Pcv, Hb, Wbc, Hct, it turns out that there is a significant decrease and the p-value is less than (0.05). As for the effect of the sex factor on the mentioned blood parameters, there is no significant effect, and the p-value is greater than (0.05). When we compare the control group with the group of Hashimoto's and Graves ' patients, we find that there is a significant decrease in Hashimoto's hematological parameters: Esr, Pcv, Hb, Wbc, Hct and that the p-value is less than (0.05), while we find that there is a significant increase in graves hematological parameters: Esr, Pcv, Hb, Hct and that the p-value is less than (0.05), while in Wbc we find a significant decrease in graves, the p-value is less than (0.05). Conclusions: We conclude from the result of the current study the following: 1-the incidence of Hashimoto's disease of hypothyroidism in the study sample is 39%, while the incidence of Graves ' disease of hyperthyroidism is 0.07%. 2-the percentage of rheumatoid disease infection compared to the total sample is 47 %. 3-we conclude from this result that rheumatoid disease, due to its high incidence in the study sample, affects the occurrence of thyroid disorders. 4-the prevalence of Hashimoto's disease increases with age. 5-the occurrence of anemia in rheumatoid patients with hypothyroidism. 6-a high percentage of patients with pain, arthritis and vasculitis, especially in graves ' patients, as a result of the effects of smoking and obesity, and this is determined by increasing Esr levels as an indicator of the level of inflammation of joints and tissues in the body. 7-an increase or decrease in the percentages and levels of Pcv, Hb, Wbc, Hct leads to an increase or decrease in blood density, which leads to an increase or decrease in blood pressure or the occurrence of anemia or a decrease in the body's immunity when the Wbc is low or inflammation of blood vessels. 8-low levels and ratios of blood parameters lead to lethargy, fatigue, headaches, a decrease in heart rate and lack of appetite for food. 9-the occurrence of hyperthyroidism in the study sample, specifically from the ages of (22-65) years, may be due to exposure to environmental pollution such as radiation or the consumption of iodine in large quantities, or the cause may be drinking alcohol, or as a result of mental disorders and diseases or following some harmful eating habits such as caffeine consumption or sugar through drinking coffee and soft drinks.